(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the interpretation of the poetic text in linguistic aspect. Акцентируется attention on interaction of figurative-conceptual and language levels of structure of the text. On an example of a linguistic perusal of M. Ryl’sky poetry the role of units of different levels of language in reflection of the ideological and art contents is shown.